2001
DOI: 10.1034/j.1600-051x.2001.028004306.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of periodontal treatment on glycemic control in patients with type 2 diabetes mellitus

Abstract: We interpret the data in the study to suggest that periodontal therapy was associated with improved glycemic control in persons with type 2 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
232
9
10

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(262 citation statements)
references
References 23 publications
11
232
9
10
Order By: Relevance
“…This result is in agreement with various other studies [51,52]. This result may be due to the fact that patients with well-controlled diabetes mellitus might respond to non-surgical therapy similarly well as healthy controls [48] and many of the patients in this study were controlled, diabetic patients.…”
Section: Latha Et Alsupporting
confidence: 82%
See 1 more Smart Citation
“…This result is in agreement with various other studies [51,52]. This result may be due to the fact that patients with well-controlled diabetes mellitus might respond to non-surgical therapy similarly well as healthy controls [48] and many of the patients in this study were controlled, diabetic patients.…”
Section: Latha Et Alsupporting
confidence: 82%
“…This is in agreement with a study by Grossi et al [49] and Kiran et al [52] who concluded that elimination of periodontal infection and improvement of periodontal inflammation significantly reduces the level of HbA1c in the short term, hence, improving diabetes metabolic control. Stewart et al [51] reported a reduction in HbA1c value from 9.5% to 7.6% 10 months following non-surgical therapy. A systematic review in 2010 concluded that periodontal therapy for type II diabetic patients is favorable and can reduce the HbA1c levels [53,54].…”
Section: Latha Et Almentioning
confidence: 99%
“…Local production of cytokines in the periodontal tissue affects glycemic control through systemic exposure and impairing intracellular insulin signaling thus potentially contributing to insulin resistance [23]. Hyperglycemic state may thus be enhanced in chronic periodontitis patients and periodontal therapy can therefore result in reduced HbA1c [24]. In this study, patients who received azithromycin showed comparatively higher reduction in HbA1c than patients who received metronidazole and SRP alone.…”
Section: Effect Of Oral Azithromycin and Metronidazole On Dental Paramentioning
confidence: 65%
“…A number of interventional studies have shown that periodontal treatment may help in the improvement of metabolic control in type 2 diabetic patients [10,11,[16][17][18][19]. However, contradictory results have been demonstrated in other studies regarding the effects of periodontal therapy on glycaemic control [20][21][22].…”
Section: Non-surgical Periodontal Therapy (Srp)-effect On Glycaemic Cmentioning
confidence: 88%